Artificial intelligence for the enhancement of television archives Case study: The heritage of Tunisian television - Besma BSIR; Kaouthar HAMED; Oumaima LAIBIDI; Abir BEN WAHADA (Journal of Information Sciences)
In this article, we explore the opportunities offered by artificial intelligence (AI) to modernize archive management within the Tunisian Television Establishment (ETT), in a context of ongoing digital transformation of public media. Although ETT does not yet operate fully functional AI systems, several cooperation projects, particularly with INA (France) and the European Union, have laid the groundwork for a more structured digital environment. The recent implementation of the MAM DALET system represents a significant milestone in the centralization and digitization of audiovisual content. We conducted our study using a qualitative approach based on field observation and document analysis. Through this, we highlight the major challenges related to the structuring, enhancement, and use of television archives, especially news broadcasts, which serve as essential records of national memory. Our findings reveal the need for a strategy tailored to the specific needs of ETT and aligned with Tunisia’s national AI deployment plan. This strategy should define clear priorities, a realistic timeline, and anticipate the necessary human, financial, and technical resources. We also recommend fostering strong partnerships, developing specialized training programs, maintaining an active technological watch, and participating in professional networks such as FIAT. In cases where internal resources are limited, we suggest considering outsourcing to specialized start-ups as a viable option. AI thus stands out as a key driver of modernization, with strong cultural, economic, and strategic potential for ETT.